Effect of high NEFA concentration on lipid metabolism disorders in hepatocytes based on lipidomics - Fan, Xinyi; Xu, Jie; Hu, Yuan; Wang, Kui; Zhao, Yiyi; Cai, Jinyin; Zhang, Xinyuan; Pan, Binghai; Xu, Anqi; Chen, Yajing; Liu, Songhao; Jiang, Kangfeng; et al. (Frontiers in Pharmacology, 2024)
High concentrations of nonesterified fatty acids (NEFA) is the key of characteristic of fatty liver in dairy cows. Therefore, the aim of this study was to investigate the effect of high concentration of NEFA on lipid metabolism in hepatocytes through the lipidomic approach and molecular biology techniques. Here, we found that high concentration of NEFA (0.6-2.4 mM) significantly reduced the cell viability in a concentration-dependent manner, indicating that high concentrations of NEFA have lipotoxicity on hepatocytes. In addition, NEFA promoted triglycerides (TAG) accumulation, increased the mRNA expression of the lipogenic molecules SREBP1c and FASN, and decreased the mRNA expression of lipolytic molecules CPT1A and HSL in hepatocytes. Mechanistically, the results of lipidomics analysis further showed that high concentration of NEFA induced lipid metabolism disorders in hepatocytes by regulating metabolic pathways such as glycerol phospholipid metabolism, glycosyl phosphatidylinositol anchored biosynthesis, triglyceride metabolism, sphingolipid metabolism, and inositol phosphate metabolism.